Risk for decreased cardiac tissue perfusion and activity intolerance: Association study - SUELLEN CRISTINA DIAS EMIDIO; Laís Pereira Giovanini; Paula Rocco Gomes Lima; Julia Leme Gonçalves; Ana Railka de Souza Oliveira-Kumakura (Universidad Nacional de Colombia, 2021)
Objective: To identify the nursing diagnoses of risk for decreased cardiac tissue perfusion and risk for activity intolerance and establish the association between the components of both diagnoses and the signs and symptoms of acute coronary syndromes. Materials and methods: Observational and associative study with 75 patients diagnosed with acute coronary syndrome in a Brazilian public hospital. Inferential statistics and multiple Poisson regression models were applied. Results: 84% of the patients showed risk for activity intolerance and 80% reported risk for decreased cardiac tissue perfusion. Risk factors were present in more than 50% of the sample. The diagnoses showed a high frequency in patients with acute coronary syndrome. Pharmacological agents, presence of comorbidities, and family and personal history were associated with the diagnoses. Absence of evidence of decreased cardiac tissue perfusion as dyspnea, radiation to shoulder and jaw, and pain time less than ten hours acted as protective factors. Conclusion: There is a high cardiovascular vulnerability of patients with acute coronary syndrome to the proposed nursing diagnoses. Therefore, we recommend further studies to determine the predictive power of the assessed risk diagnoses for those focusing on this health problem.